Analisis survival: Pemenuhan kebutuhan penggunakan kontrasepsi pada orang dengan HIV/AIDS (ODHA) - Dewi Aprelia Meriyani; Ketut Putra Sedana; Putu Sukma Megaputri (Holistik Jurnal Kesehatan, 2023)
Background: The use of contraception in women with HIV/AIDS is one of the 4 goals of preventing HIV transmission. The use of contraception is done to prevent unwanted pregnancy and prevent transmission. However, currently the number of unmet needs for contraceptive use among WUS with HIV is high and many WUS with HIV are not exposed to contraceptive use.Purpose: To examine the survival of WUS contraceptive use with HIV and to see differences in length of use depending on the type of contraception chosen.Method: The research method uses a retrospective study using secondary data to assess contraceptive visits starting from the first time you become an acceptor and the last visit to receive contraceptive services. The sample taken was 105 respondents (female) from various health centers spread across Buleleng Regency. The analysis used was survival analysis using Kaplan-Meier and Kruskall Wallis to see group differences in types of contraception.Results: The results showed that the mean and median survival was quite wide between the group using condoms, 3-month injections, MOW contraception and the group not using contraception. This is significant with a chi square value of 10.82 and a p value <0.05, namely 0.013. The type of group that uses condom contraception also has the highest mean and is significantly different from other contraceptive groups.Conclusion: In terms of survival, PLWHA women who use condom contraception have a lifespan of 37 months or the equivalent of 3 years to become unmet need.Keyword: Contraception; Female; People Living With HIV/AIDS (PLWHA); Unmet NeedPendahuluan: Penggunaan kontrasepsi pada wanita ODHA merupakan salah satu tujuan dari 4 prong pencegahan penularan HIV. Penggunaan kontrasepsi dilakukan untuk mencegah kehamilan yang tidak diinginkan dan melakukan pencegahan penularan. Namun saat ini angka unmet need penggunaan kontrasepsi WUS dengan HIV masih tinggi dan banyak WUS HIV tidak terpapar oleh penggunaan kontrasepsi.Tujuan:  Untuk melihat perbedaan lama terhadap survival dalam penggunaan kontrasepsi pada wanita ODHA.Metode: Penelitian menggunakan studi retrospektif menggunakan data sekunder untuk menilai kunjungan kontrasepsi dimulai dari awal menjadi akseptor dan terakhir berkunjung mendapatkan pelayanan kontrasepsi. Sampel yang diambil sebanyak 105 responden (wanita) dari berbagai puskesmas yang tersebar di Kabupaten Buleleng. Analisis yang digunakan adalah survival analisis dengan Kaplan-meier dan kruskall wallis untuk melihat perbedaan kelompok jenis kontrasepsi.Hasil: Hasilnya bahwa mean dan median survival cukup lebar dari kelompok pengguna kontrasepsi kondom, suntik 3 bulan, MOW dan kelompok yang tidak menggunakan kontrasepsi. Hal ini bermakna dengan nilai chi square 10,82 dan nilai p <0,05 yaitu sebesar 0,013. Jenis kelompok pengguna kontrasepsi kondom juga memiliki mean terbanyak serta signifikan berbeda dari kelompok kontrasepsi lainnya.Simpulan: Secara survival wanita ODHA yang menggunakan kontrasepsi kondom memiliki ketahanan selama 37 bulan atau setara 3 tahun untuk menjadi unmet need.